DYNAMYCS OF USE OF SEMANTIC NEOLOGISMS IN SPANISH-LANGUAGE NEWSPAPER DISCOURSE DURING THE COVID-19 EPIDEMIC - Tsymbal , Mariia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is dedicated to the analysis of cases of the use of semantic neologisms created in Spanish-language newspapers due to the spread of the Covid-19 pandemic. Based on the materials of Spanish-language journalistic publications of the pandemic period, the article examines and analyzes cases of the use of such semantic neologisms. The study of semantic neologisms allows us to trace the changes that the realities of the epidemic have made on the meaning of units already existing in the language. The article pays attention to the characteristics of the use of neologisms in different sections of Spanish-language newspapers and the dynamics of their use compared to publications before the spread of the epidemic. A neologism is a new lexical unit that appears in the language, as well as a new meaning of an already existing unit or a new phrase. A semantic neologism is a new lexical unit that appears in the language due to the acquisition of a new meaning by a word, or by the preservation of the original meaning and the acquisition of an additional one by the same lexeme. Journalistic discourse is a type of institutional communication aimed at informing and influencing the mass addressee in the public-political, social-cultural fields and the mass media.__________References:• Попкова, О. А. Комунікативно-прагматичний потенціал складних слів періоду пандемії (на матеріали українських газетних текстів) (2021).• Diccionario de la Lengua Española: la 23ª edición (2014).• Guerrero Ramos, G. Neologismos en el español actual (Madrid: Arco/Libros, 1995).• Gutiérrez Araus, et al. Introducción a la lengua española (Madrid: Editorial Centro de Estudios Ramón Areces, 2005).• Esteban Asencio, L. «Neologismos y Prensa.» AnMal Electrónica 25 (2008).• Esteban Asencio L. ISSN 1697-4239• Maria Teresa Cabré Castellví. «La clasificación de neologismos: una tarea compleja.» Alfa, São Paulo50 (2) (2006): 229-250.• Quiroz, C. G., Pareja, A., Valencia, E., Enriquez, Y., De Leon, J., y Aguilar, P. «Un nuevo coronavirus, una nueva enfermedad: COVID-19.» Horizonte Médico, 20 (2) (2020).• ABC (https://www.abc.es/)• https://www.abc.es/espana/castilla-leon/abci-aranda-duero-recurrira-ante-tribunales-cierre-hosteleria-interior-municipio-202105102146_noticia.html• https://www.abc.es/salud/enfermedades/estudio-vincula-sintomas-neuropsiquiatricos-marcador-precoz-alzheimer-20220830190111-nt.html• https://www.abc.es/familia/padres-hijos/abci-ninos-pandemials-generacion-incognita-202104150114_noticia.html• https://www.abc.es/sociedad/abci-abrazos-besos-choque-codos-estas-formulas-correctas-para-saludarse-tiempos-coronavirus-202009112242_noticia.html• El País (https://elpais.com/)• https://elpais.com/espana/catalunya/2020-05-17/uno-de-los-errores-fue-no-tener-equipos-de-vigilancia-epidemiologica-potentes.html• https://elpais.com/espana/catalunya/2022-01-20/reinfecciones-y-omicron-que-conocemos.html• https://elpais.com/ideas/2020-06-26/chinofobia.html?rel=buscador_noticias• https://elpais.com/sociedad/2022-01-29/la-curva-epidemica-en-espana-consolida-su-descenso-pero-los-expertos-llaman-a-la-cautela.html• La Vanguardia (https://www.lavanguardia.com/)• https://www.lavanguardia.com/vida/20211228/7957576/sanidad-comunidades-estudiaran-reducir-cuarentena-contactos.html• https://www.lavanguardia.com/local/madrid/20201016/484111892164/madrid-primera-residencia-ancianos-cuidados-covid-coronavirus.html• https://www.lavanguardia.com/cultura/culturas/20210130/6207320/pandemia-covid-diccionario.html• https://www.lavanguardia.com/vida/20200420/48622459327/trilla-riesgos-pasaporte-inmunidad-coronavirus.html• https://www.lavanguardia.com/vida/20211228/7957576/sanidad-comunidades-estudiaran-reducir-cuarentena-contactos.html• Sur (https://www.diariosur.es/)• https://www.diariosur.es/sociedad/salud/expertos-recomiendan-mascarillas-20200121191504-nt.html?ref=https%3A%2F%2Fwww.google.com%2F• El Comercio (https://elcomercio.pe/)• https://elcomercio.pe/opinion/mirada-de-fondo/las-estadisticas-de-la-pandemia-por-ivan-alonso-noticia/• https://elcomercio.pe/tecnologia/ciencias/coronavirus-en-el-peru-como-cuidar-nuestra-salud-mental-en-el-aislamiento-noticia/• Pagina 12 (https://www.pagina12.com.ar/)• https://www.pagina12.com.ar/257085-webcomics-y-humor-grafico-contra-el-aislamiento#:~:text=En%20situaci%C3%B3n%20de%20pandemia%2C%20la,un%20evento%2C%20ah%C3%AD%20est%C3%A1%20internet• https://www.pagina12.com.ar/254118-en-plena-cuarentena-por-el-coronavirus-aplausazo-para-les-tr
Keywords: neology, semantic neologism, pandemic, newspaper discourse, press, Spanish newspapers